Question
Asked Dec 9, 2019
1 views
Given f(x) = 6/x and g(x) = 6x, find the following expressions.
(b) (go f)(2) (c) (fo f)(1) (d) (g • g)(0)
(a) (fo g)(4)
(a) (fo aV4) =.
help_outline

Image Transcriptionclose

Given f(x) = 6/x and g(x) = 6x, find the following expressions. (b) (go f)(2) (c) (fo f)(1) (d) (g • g)(0) (a) (fo g)(4) (a) (fo aV4) =.

fullscreen
check_circle

Expert Answer

Step 1

Since we are entitled to answer up to 3 sub-parts, we’ll answer the first 3 as you have not mentioned the subparts you need help with. Please resubmit the question and specify the other subparts you’d like to get answered.

Given:

help_outline

Image Transcriptionclose

f (x) = 6Vx and g(x)=6x

fullscreen
Step 2

(a). Find (f o g) (4):

help_outline

Image Transcriptionclose

(Гog)-/(<(*)) [ 8()- б:] (Гоз)-/(6х) 6х (Гog)-6/бт (Гog)(4)-6/6х4 (Гog)(4)-6/24 (Гog)(4)-6х26 Гoз/(4) -12/6

fullscreen
Step 3

(b). Find (g o ...

help_outline

Image Transcriptionclose

(gof)=g(f(x)) [ /(x)=6\F] (805)=8(6Vx) (gof)=6x6x (g0f)=36 (8of)(2)=36/2|

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Solutions are written by subject experts who are available 24/7. Questions are typically answered within 1 hour.*

See Solution
*Response times may vary by subject and question.
Tagged in

Math

Algebra

Other